Competitividade na pequena produção agroindustrial: estudo na agroindústria da castanha de caju - Andrade Neto, Júlio César de (2006)
This paper looks into the cashew nut industrial process as a factor in adding value to it and involves its productions, industrialization and marketing. Its competitiveness fundamentally depends in its ability to surpass technological and non technological difficulties that contributes to increase costs and diminishes attributes to better qualities which means values to the market. The methodology applied in this paper was application of a questionnaire with a Likert model scale with closed questions and constituted by variables that composed nominated groups: exporting obstacles, market strategy, competitive advantages, broken nuts index, productive potential and social-economic profile of members of the Cooperative. A descriptive analysis was the method employed for the data analysis. After identifying some of the quantitative gains in the industrial process of the cashew nuts, recommendations are presented to COOPERCAJU to promote courses to improve the members productivity as well as technical assistance, in order to get more efficacy in the cashew nuts industrial processing